Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1961
DOI: 10.1063/1.1728433
|View full text |Cite
|
Sign up to set email alerts
|

Transitions and Relaxations in Polytetrafluoroethylene

Abstract: The modulus and internal friction of polytetrafluoroethylene were measured with longitudinal waves at a frequency of 12 Mc between 248° and 548°K and the fluorine magnetic resonance was studied between 77° and 375°K. The samples covered a wide range of crystallinities and included a specimen which had not been sintered (as polymerized material which had not been heated above the melting temperature). The results resolve discrepancies which existed in the literature and introduce new information about the relax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1965
1965
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…3. We previously overlooked the paper by Eby and Sinnott (67) which showed that the glass 11 process corresponded to about 5 CF, groups which is about right for a crankshaft. (68) ( 6 9 ) . )…”
Section: C8-238mentioning
confidence: 99%
“…3. We previously overlooked the paper by Eby and Sinnott (67) which showed that the glass 11 process corresponded to about 5 CF, groups which is about right for a crankshaft. (68) ( 6 9 ) . )…”
Section: C8-238mentioning
confidence: 99%
“…From DSC measurement at low temperatures, Lau et al showed that broad transition from about −113 to −33 °C occurred, with a midpoint at about −73 °C 34. Mechanical measurements at low frequencies (torsion experiments) indicated amorphous relaxations at about −100 and 130 °C,35, 36 whereas in ultrasonic measurements relaxations were observed at −10 and 197 °C 37. From DMA at 1 Hz, the γ (Glass I) and α (Glass II) relaxation temperatures of −80 and 126 °C, respectively, were reported.…”
Section: Resultsmentioning
confidence: 99%
“…support from the fact that the formation of branched chains in ~he polymerization of C2F 4 would involve the breakmg of C-F bonds, which are relatively stro.ng [1] . The average number of CF2 groups per ch am has been found to vary from 3,000 for specially prepared low-molecular-weight sa mples to as high ~s 180,000 for samples similar to those of industrial lI1terest .…”
Section: Introductionmentioning
confidence: 99%
“…In the amorphous regions of the polymer, glass transitions have been detected at about -97 0 and 127 DC, where motions of sequences of CF2 groups are believed to set in. Eby and Sinnott [4] believed that the rise of internal friction above 240 DC in a 95-percent-crystalline sample may be the result of additional but hitherto unresolved crystalline relaxations. The generally accepted melting point of the crystalline polymer is 327 DC, where all opacity was observed to disappear on heating [5].…”
Section: Introductionmentioning
confidence: 99%